REALIZATION OF COLLABORATIVE LEARNING IN SPEAKING SKILL - Ardriyati, Wienny (Proceeding SENDI_U, 2018)
The aim was to find out the use of collaborative learning was effective or not to teach speaking skill and what problems occur through teaching collaborative learning. The subjects were 36 students. In this research it used pre-test and post-tests. Based on the result of pre-test which was carried out in pre-cycle, the subjects' speaking skill was low (43.75). The result of mean score of post-test in cycle I was 56.81 and post-test of cycle II was 71.11. These findings showed the fact that the mean score of pre-test was lower than the mean scores of cycle I and cycle II. The significance difference figures further suggest that cycle II was more effective than cycle I. These findings clearly discovered that the students' speaking skill was successfully effective through collaborative learning. The effectiveness of this strategy was supported by the data of the questionnaires which clearly showed that 35.71% of the subjects didnt strongly agreed of this strategy. These findings showed 62.71 of the subjects attitude and motivation in speaking about the expression of four types of pollution through collaborative learning were very positive.